2017
DOI: 10.7860/jcdr/2017/20858.9341
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia: A Cross-sectional Study to Assess Mobile Phone Usage Among Dental Students

Abstract: Introduction: Mobile phones were originally seen as a gadget for communication but currently, the internet enabled mobile phones have become an integral part of our daily life. Their benefits are incomparable but at the same time, they have some negative effects too. Aim:To assess the pattern of usage of mobile phones and its effects on the academic performance of students. Materials and Methods:A descriptive cross-sectional study was conducted amongst 554 students of D. J. College of Dental Sciences and Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 7 publications
7
76
3
9
Order By: Relevance
“…And also a negative correlation found with the overall grade of the first semester of the 2016/2017 school year and the 3 dimensions of Nomophobia which means that students with good academic performance are not too attached to their smartphone and the social media. Another study showed that 39.5% of students perceived their academic performance to be poorer due to spending of more time on phone and the association was statistically significant (p< .05) (Prasad, et al, 2017), the results of Gezgin, et al (2018), adolescents were at a moderate level. A study conducted by Dixit S et al, in 2010 revealed that 18.5% of students were Nomophobic as well as the highest number of students being Nomophobic were from 3rd professional part-I (7%) and the least number of students were from internship (1%).…”
Section: Discussionmentioning
confidence: 94%
“…And also a negative correlation found with the overall grade of the first semester of the 2016/2017 school year and the 3 dimensions of Nomophobia which means that students with good academic performance are not too attached to their smartphone and the social media. Another study showed that 39.5% of students perceived their academic performance to be poorer due to spending of more time on phone and the association was statistically significant (p< .05) (Prasad, et al, 2017), the results of Gezgin, et al (2018), adolescents were at a moderate level. A study conducted by Dixit S et al, in 2010 revealed that 18.5% of students were Nomophobic as well as the highest number of students being Nomophobic were from 3rd professional part-I (7%) and the least number of students were from internship (1%).…”
Section: Discussionmentioning
confidence: 94%
“…Today's smartphones present great opportunities and comforts for people; at the same time, they facilitate the accomplishment of tasks and have achieved generalized popularity in the present society [1] thanks to their communicative power and people's engagement with them [2]. The users of this technology even state that it has become an extension of their body, determining both their identity and their way of being [3].…”
Section: Introductionmentioning
confidence: 99%
“…Then, Prasad et al mentioned that the objective of the study is to evaluate the pattern of usage of mobile phones and its effects on the academic performance of dental students in India College. The authors concluded that there is an alarming indication of mobile phone addiction on the part of students, which affects their academic performance in a negative way [21]. Arpaci et al presented a study that aims to investigate the mediating effect of mindfulness on the relationship between attachment and nomophobia.…”
Section: Introductionmentioning
confidence: 99%